2020
DOI: 10.24252/elite.v7i1a7
|View full text |Cite
|
Sign up to set email alerts
|

Online Writing Exchange With Overseas Students: Efl Learners’ Errors and Perceptions

Abstract: Writing skill is crucial for non-English students, like agriculture students because students are required to write an abstract of bachelor thesis in English. Nowadays, writing is not only conducted conventionally i.e. using paper and pencil, but also using the internet through online writing exchange. Several studies regarding students’ writing errors have been conducted but error analysis of agriculture students’ writing using online writing is still less researched. To fill this gap, the present study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…One of the major errors that students committed when using mechanics in writing was using commas and capitalization (Fasikh & Murtadho, 2019). This supported a result of a study conducted on errors analysis of students writing, which indicated that one of the most mistakes found in students' writing was misplacing the comma or neglecting to put the comma in the right place (Prasetianto & Maharddhika, 2020). Some students did not use a comma before conjunctions when trying to create compound sentences (Fauzan, Aulya, & Noor, 2020).…”
Section: Commassupporting
confidence: 53%
“…One of the major errors that students committed when using mechanics in writing was using commas and capitalization (Fasikh & Murtadho, 2019). This supported a result of a study conducted on errors analysis of students writing, which indicated that one of the most mistakes found in students' writing was misplacing the comma or neglecting to put the comma in the right place (Prasetianto & Maharddhika, 2020). Some students did not use a comma before conjunctions when trying to create compound sentences (Fauzan, Aulya, & Noor, 2020).…”
Section: Commassupporting
confidence: 53%
“…Students need to be prepared to create professional reports or letters. Prasetianto and Maharddhika (2020) revealed the importance of the development of writing competence by stating that "writing skill is also needed for their professional work in doing business and to get a good International English Language Testing System (IELTS) score band as a scholarship requirement" (p. 75). This is also consistent with what Fasikh and Murtadho (2019) explored "the ability to write well is also an asset in most careers…search for a job usually requires a letter of application and a resume" (p. 87).…”
Section: Introductionmentioning
confidence: 99%
“…Next, a study found that asynchronous peer feedback helped Taiwanese students in writing sentences (Shang, 2017). A study analyzed agriculture students' writing errors in an online environment (Prasetianto & Maharddhika, 2020). In addition, teaching techniques in online learning have been proposed, such as online literature circle, cooperative learning, CAFÉ instructional design (Ferdiansyah et al, 2020;Ivone et al, 2020;Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%